2013
DOI: 10.1021/pr400115q
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomic Profiling of Secreted Products from Pancreatic Islet Culture Results in a Higher Yield of Full-length Peptide Hormones than Found using Cell Lysis Procedures

Abstract: Peptide Hormone Acquisition through Smart Sampling Technique-Mass Spectrometry (PHASST-MS) is a peptidomics platform that employs high resolution liquid chromatography-mass spectrometry (LC-MS) techniques to identify peptide hormones secreted from in vitro or ex vivo cultures enriched in endocrine cells. Application of the methodology to the study of murine pancreatic islets has permitted evaluation of the strengths and weaknesses of the approach, as well as comparison of our results with published islet studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 46 publications
(66 reference statements)
4
36
0
Order By: Relevance
“…Their results confirmed that GLP-1 was produced in and secreted from human islets, specifically the α cells. In a more recent study, Taylor et al (2013) employed Peptide Hormone Acquisition through Smart Sampling Technique-Mass Spectrometry (PHASST-MS), an advanced peptidomics platform that employs high resolution liquid chromatography-mass spectrometry (LC-MS), to identify secreted peptide hormones, and reported that both full-length GLP-1(1–37) and bioactive GLP-1(7–37) were detected in the media of cultured human islets (Taylor, et al 2013). All of these studies support the presence of a local GLP-1 production system within the pancreatic islets.…”
Section: Emerging Evidence Supporting Glp-1 Production In Pancreatmentioning
confidence: 99%
“…Their results confirmed that GLP-1 was produced in and secreted from human islets, specifically the α cells. In a more recent study, Taylor et al (2013) employed Peptide Hormone Acquisition through Smart Sampling Technique-Mass Spectrometry (PHASST-MS), an advanced peptidomics platform that employs high resolution liquid chromatography-mass spectrometry (LC-MS), to identify secreted peptide hormones, and reported that both full-length GLP-1(1–37) and bioactive GLP-1(7–37) were detected in the media of cultured human islets (Taylor, et al 2013). All of these studies support the presence of a local GLP-1 production system within the pancreatic islets.…”
Section: Emerging Evidence Supporting Glp-1 Production In Pancreatmentioning
confidence: 99%
“…; Taylor et al. ). A further peptide, closely related to GRPP, GRPP‐like peptide (GRPP‐LP) was also identified in Wistar rat islets (Stewart et al.…”
Section: Introductionmentioning
confidence: 98%
“…Peptidomics attempts to perform a quantitative and qualitative analysis of peptides in a given cell type, tissue or disease state. Through this method, a large number of both intracellular and secreted mammalian peptides have been identified [4][5][6][7][8][9]. Peptides are important bioactive molecules in their own right.…”
Section: Introductionmentioning
confidence: 99%